2010
DOI: 10.1021/ol102562k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photosensitized Singlet Oxygen Generation Efficiency of Novel Aza-BODIPY Dyes

Abstract: Novel aza-BODIPY derivatives substituted with heavy atoms such as bromine and iodine were synthesized, and their triplet and singlet oxygen generation efficiencies have been investigated. These derivatives showed absorption in the NIR region with high molar extinction coefficients. The dye substituted with four iodine atoms showed yields of Φ(T) = 0.78 and Φ((1)O(2)) = 0.70, which are the highest values so far obtained for the aza-BODIPY derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
198
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(210 citation statements)
references
References 40 publications
(14 reference statements)
5
198
0
Order By: Relevance
“…Compound 2 which has two iodine atoms at the 2,6 position was used as the reference since iodine containing compounds are known to sensitize singlet oxygen generation. Rapid DPBF oxidation in compound 2 is consistent with the well-known fact that iodine increases singlet oxygen generation due to the heavy atom effect [39,40]. Compound 4 which has one 3-ethynylthiophene unit and one iodine showed only slight decrease in oxidation rate in comparison to compound 2 ( Figure 3).…”
Section: Singlet Oxygen Generationsupporting
confidence: 82%
“…Compound 2 which has two iodine atoms at the 2,6 position was used as the reference since iodine containing compounds are known to sensitize singlet oxygen generation. Rapid DPBF oxidation in compound 2 is consistent with the well-known fact that iodine increases singlet oxygen generation due to the heavy atom effect [39,40]. Compound 4 which has one 3-ethynylthiophene unit and one iodine showed only slight decrease in oxidation rate in comparison to compound 2 ( Figure 3).…”
Section: Singlet Oxygen Generationsupporting
confidence: 82%
“…Figure 8p resents, for comparison, the structures, triplet state properties and singlet oxygen formation quantum yields of all halogenated aza-BODIPYs reportedu ntil 2017. [35,41,64,65] We demonstrated that the iodinated aza-BODIPYs 5-8,i n contrastt ot he non-iodinated counterparts 1-4,p roduce highly populated triplet state upon excitation, as evidenced by the observation of transient absorption spectra and lack of room-temperature emission from the singlet excited state (S 1 !S 0 ). In addition, iodinated aza-BODIPYs 5-8 efficiently harvest visible light, as evidenced by their relatively high molar absorption coefficients (e), viz.…”
Section: Discussionmentioning
confidence: 95%
“…Owing to their advantageous and tunable photophysical properties and ability to generate singlet oxygen ( 1 O 2 )c oupled with absorption of light from the socalled "therapeuticw indow"( 600 nm-1100 nm), aza-BODIPY dyes have been proposed as potential triplet photosensitizers for both anti-microbiala nd anti-cancer photodynamic therapy. [20,[30][31][32][33][34][35][36][37][38][39][40][41] Aza-BODIPYs continue to attracta ttention as chemosensors for the detection of ammonia, [42] cysteine, homocysteine and glutathione in living cells, [43] Hg 2 + , [44][45][46] F À , [47,48] in vivo detection of H 2 S, [49] carbon dioxide, [50] glucosei nw hole blood, [51] detection of saxitoxin [52] and pH-sensitive sensors. [52] Furthermore, aza-BODIPYs have been proposed as photoactive components in photovoltaic devices [54][55][56] and nonlinear optical materials.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Although heavyatom-free organic triplet photosensitizers do exist, such as porphyrins or perylenedimides [22] and the recently reported C 60 dyads for TTA upconversion, [17d, e] it is clear that the molecular diversity needs to be increased substantially. Unfortunately, the rules of molecular structure design acquired in the study of fluorophores are not really applicable to the triplet-state manifold.…”
Section: Introductionmentioning
confidence: 99%